Online Media Audience during the COVID-19 Pandemic as an Active Amplifier of Disinformation: Motivations of University Students to Share Information on Facebook - Tkáčová, Hedviga; Maturkanič, Patrik; Pavlíková, Martina; Slobodová Nováková, Katarína (Communication Today, 2024)
Disclosure of disinformation has attracted increasing attention in recent years. The society recognises that false reports pose a real threat to the credibility of information and, ultimately, to the security of society. On the Internet an active audience is a distributor of media content because they are convinced of its truth, and in the online environment they find it in other people. Therefore, the audience seems to be an active amplifier of disinformation (sharing), and thus explicitly as a creator of (unwanted) web content (sharing and commenting). People’s willingness to share disinformation is linked to people’s similar attitudes; it is related to the similarity of faith and to the perception of the message, considered as appropriate and interesting (“I like it”), etc. The term “homogeneity” turns out to be a key term in audience research, and experts speak about a phenomenon that in fact appears to be the main driving force for the dissemination of any content. The aim of the research is to identify and classify the factors that motivate university students to share information on the social networking site Facebook.